2020
DOI: 10.1073/pnas.2004615117
|View full text |Cite
|
Sign up to set email alerts
|

TNF deficiency dysregulates inflammatory cytokine production, leading to lung pathology and death during respiratory poxvirus infection

Abstract: Excessive tumor necrosis factor (TNF) is known to cause significant pathology. Paradoxically, deficiency in TNF (TNF−/−) also caused substantial pathology during respiratory ectromelia virus (ECTV) infection, a surrogate model for smallpox. TNF−/−mice succumbed to fulminant disease whereas wild-type mice, and those engineered to express only transmembrane TNF (mTNF), fully recovered. TNF deficiency did not affect viral load or leukocyte recruitment but caused s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 73 publications
(88 reference statements)
6
64
0
Order By: Relevance
“…Disease and Increases Survival Rates. The increased production of a number of inflammatory cytokines in mice infected with mutant ECTV possibly contributed to the increased morbidity and mortality, as shown previously in ECTV-infected TNF −/− mice (41). We postulated that the in vivo blockade of some of these cytokines might reduce the severity of the clinical symptoms and lung pathology and possibly allow the recovery of mice infected with ECTV ΔCrmD or ECTV Rev.SECRET .…”
Section: Blockade Of Ifn-γ Il-6 Il-10r or Tnf Reduces Weight Loss Andsupporting
confidence: 55%
See 3 more Smart Citations
“…Disease and Increases Survival Rates. The increased production of a number of inflammatory cytokines in mice infected with mutant ECTV possibly contributed to the increased morbidity and mortality, as shown previously in ECTV-infected TNF −/− mice (41). We postulated that the in vivo blockade of some of these cytokines might reduce the severity of the clinical symptoms and lung pathology and possibly allow the recovery of mice infected with ECTV ΔCrmD or ECTV Rev.SECRET .…”
Section: Blockade Of Ifn-γ Il-6 Il-10r or Tnf Reduces Weight Loss Andsupporting
confidence: 55%
“…WT and TNF −/− mice do not express detectable levels of IFNγ, IL-6, IL-10, TGF-β, and TNF (WT mice only) (41). The cytokine responses to ECTV WT infection in WT and TM lungs were similar, whereas the levels of most mRNA transcripts were significantly higher in TNF −/− lungs compared to WT or TM lungs (Fig.…”
Section: Absence Of Crmd Results In Dysregulated Expression Of Proinflammatorymentioning
confidence: 87%
See 2 more Smart Citations
“…It has been shown that TNF- α did not play a pivotal role in the clearance of viral infections such as influenza and poxvirus, while TNF-α depletion dysregulates antiviral inflammation. Highly expressed TNF-α results in lung tissue fibrotic remodeling by inducing uncontrolled recruitment of immune cells and decreased level of antioxidant molecules in parenchymal and endothelial cells of lung tissue [ 34 , 35 ]. TNF- α activates the host cells' extrinsic apoptotic pathway by activating death receptors TNFR1, Fas, and TNF-related apoptosis-inducing ligand (TRAIL) [ 36 , 37 ].…”
Section: Mscs As a Potential Therapy For Severe Cases Of Covid-19mentioning
confidence: 99%